2020
DOI: 10.1111/jan.14680
|View full text |Cite
|
Sign up to set email alerts
|

A model for predicting 7‐day pressure injury outcomes in paediatric patients: A machine learning approach

Abstract: Aims We sought to explore factors associated with early pressure injury progression and build a model for predicting these outcomes using a machine learning approach. Design A retrospective cohort study. Methods In this study, we recruited paediatric patients, with hospital‐acquired stage I pressure injury or suspected deep tissue injury, who met the inclusion criteria between 1 January 2015–31 October 2018. We divided patients into two groups, namely healing or delayed healing, then followed them up for 7 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…No studies could be found to adopt intelligent tutoring systems or adaptive systems and personalization. For example, Chun et al 12 investigated factors related to early pressure injury progression and applied a machine learning approach to develop a model to predict these outcomes. In terms of aspects of nursing education, the most adopted roles of AI were profiling and prediction (two out of four studies) and intelligent tutoring systems (two studies), whereas no research could be found to adopt assessment and evaluation or adaptive systems and personalization.…”
Section: Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No studies could be found to adopt intelligent tutoring systems or adaptive systems and personalization. For example, Chun et al 12 investigated factors related to early pressure injury progression and applied a machine learning approach to develop a model to predict these outcomes. In terms of aspects of nursing education, the most adopted roles of AI were profiling and prediction (two out of four studies) and intelligent tutoring systems (two studies), whereas no research could be found to adopt assessment and evaluation or adaptive systems and personalization.…”
Section: Research Resultsmentioning
confidence: 99%
“…6,10 In recent years, the application of AI in the nursing field has been recognized by several researchers. 4,12,13 The review studies on the application of AI in the nursing field have mainly focused on nursing pain education, 3 primary care, 4 and AI agents in healthcare. 5 Few studies could be found that reviewed papers on AI in nursing activities.…”
mentioning
confidence: 99%